La valoración de la prueba y su incidencia en las resoluciones administrativas disciplinarias, tramitadas en la dirección provincial de Chimborazo del consejo de la judicatura, durante el año 2021 - Pillajo Carvajal, Edwin Lenin (2023)
ABSTRACT: The thesis "The assessment of evidence and its impact on administrative disciplinary resolutions, processed in Dirección Provincial de Chimborazo del Consejo de la Judicatura, during the year 2021", aimed to analyze disciplinary proceedings substantiated by Dirección Provincial del Consejo de la Judicatura de Chimborazo, during the year 2021, to determine what are the parameters of evidentiary assessment and its impact on the resolutions adopted in the processes followed against judicial servants, in order to reach this objective, three specific objectives were proposed: firstly, the parameters of evidentiary assessment that have been adopted in these resolutions were examined, identifying the evidentiary dynamics, the burden of proof on whom it falls; secondly, a comparative law study was conducted on the assessment of evidence in the administrative and judicial spheres, in order to determine whether in administrative matters this evidentiary assessment is different and what its elements are; and thirdly, a standard of evidentiary assessment was proposed; Third, a standard of proof was proposed to be used by public servants at the time of resolving disciplinary processes in Direcciones Provinciales del Consejo de la Judicatura. A broad study of the theory of evidence was carried out, and in order to verify the hypothesis proposed, surveys were applied through questionnaires to lawyers in free practice who have sponsored disciplinary processes in Dirección Provincial del Consejo de la Judicatura, to officials who are the judicial substancers and servants subjected to this type of processes, concluding at a general level that the evaluation of the evidence that is carried out in this institution is erroneous because it is not based on a standard of evidence, so recommendations are made to improve this transcendental aspect that affects fundamental rights and guarantees of due process.